Diskresi Kepolisian dalam Penegakan Hukum Tindak Pidana Kekerasan Seksual: Studi Kasus Polrestabes Medan - Eunike Br Simanjuntak; Sri Hadiningrum (Legalite : Jurnal Perundang Undangan dan Hukum Pidana Islam, 2025)
This study aims to examine the implementation of police discretion in handling sexual violence cases at Polrestabes Medan and to analyze its effectiveness from the perspectives of victim protection and restorative justice. This research employs an empirical legal research design with a qualitative approach, utilizing in-depth interviews, observation, and document analysis as data collection techniques. The findings indicate that police discretion plays a strategic role in preventing revictimization, facilitating victim recovery, and realizing a more humane and victim-centered form of justice. Nevertheless, its implementation remains constrained by normative inconsistencies, institutional limitations, and socio-cultural challenges, particularly regulatory disharmony and limited professional capacity. Therefore, strengthening regulatory frameworks and embedding victim-centered justice principles are essential to optimizing police discretion in addressing sexual violence cases.